Dissolution test for oral suspension: an overview about use and importance - Thaís dos Santos Paulino Soares; Jacqueline de Souza; Lorena de Sousa Rosa; Flávia Dias Marques-Marinho (Universidade de São Paulo, 2022)
Abstract This work aims to ascertain the comprehensiveness of dissolution tests for oral suspensions registered in Brazil and the USA. After consulting literature since 1994, a paucity of information about dissolution methods for suspensions was detected. It makes it difficult to establish the most appropriate test parameters. In January, 2019, there were 46 drugs registered in Anvisa (Brazil) as oral suspension, being 47 reference, 173 generic and 114 interchangeable similar (IS) medicines; while in the USA, 90 drugs were registered as oral suspension by FDA, 235 Abreviatted New Drug Application and 111 New Drug Application medicines. Out of 46 and 90, only six and 15 drugs as oral suspension had a pharmacopeial dissolution test, corresponding to 70 (20.9%) and 82 (23.7%) products in Brazil and the USA, respectively. Dissolution studies were found for 17 drugs as oral suspension in the non-compendial literature. Dissolution test conditions were established to few marketable oral suspension drugs, most of which are BCS class II or IV. Thus, investing in dissolution studies could subsidize the registration of these products by regulators, especially for generic and IS drugs, by comparing dissolution profiles, and predicting their in vivo behavior to avoid exposure of healthy individuals to clinical research.